Ze Stobiernej, Głogowa i Rzeszowa w daleki świat. Przypomnienie sławnego współziomka - Bachórz, Józef (Tematy i Konteksty, 2011)
The article reminds about Ludwik Nabielak, born in the vicinity of Rzeszów, an insurgent during the November Uprising and an active member of the Great Emigration. His name cannot be overlooked in any considerable research interested in Polish uprisings, mostly in the November Uprising, in the emigration known as the Great one and, more generally, in Polish literature of Romanticism. Streets of his name can be found in Warsaw, Cracow, Wrocław, Przemyśl, Jarosław and Żyrardów – before the Second World War there used to be one in Lviv as well. At least an essential biographical entry about Nabielak can be found in every Polish universal encyclopedia. The November Uprising is the subject discussed in numerous scholar and popular publications that mention his name many times. However, the name of Nabielak should be remembered not only due to his participation in the Uprising discussed at history lessons, but also due to the fact that the Polish list of obligatory readings for highschool students includes the third part of Dziady by Mickiewicz that mentions the name in one of the passages. Therefore the article refers to the biography of the famous Pole not only in the context of historical facts but also with the usage of literary references to Nabielak that can be found in romantic literature (Mickiewicz, Norwid, Goszczyński).